Profitability, Growth and Efficiency in the US Life Insurance Industry - SEGAL, Dan (Institutional Knowledge at Singapore Management University, 2004)
This study explores the relationship between cost inefficiency and profitability in the U.S. life insurance industry. Earnings have particular importance to life insurance companies because earnings and capital determine the viability of the insurer. Since the life insurance industry is mature and highly competitive, cost efficiency may be the main driver of profitability. We derive cost efficiency using the stochastic frontier (SF) method allowing themean inefficiency to vary with organizational form and the outputs. In addition, the estimation of the cost efficiency measure takes into account the underlying accounting concepts that generate the data and, consequently, the product mix (long-duration policies vs. short-duration policies) to avoid distorted estimates. Our results suggest that cost inefficiency in the life insurance industry is substantial relative to earnings, and that inefficiency is negatively associated with profitability measures such as the return on equity. The analysis of inefficiency and organizational form suggest that stock (shareholder-owned) companies are as efficient and profitable as mutual (policyholder-owned) companies.